DAMPAK FOREIGN DIRECT INVESTMENT, NILAI TUKAR, TENAGA KERJA, DAN KETERBUKAAN PERDAGANGAN TERHADAP PERTUMBUHAN EKONOMI INDONESIA DENGAN EKSPOR SEBAGAI VARIABEL MEDIATOR - Reski Nasvar Azis Madinda; Denny Saputera (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the impact of Foreign Direct Investment (FDI), exchange rates, labor force participation, and trade openness on Indonesia’s economic growth, with exports serving as a mediating variable. Economic growth is a crucial indicator of national development and reflects the ability of a country to improve public welfare. The research employs a quantitative approach using secondary time-series data from 2012 to 2024 obtained from the World Bank’s World Development Indicators. The analytical method applied is path analysis using SPSS 27.0 to examine both direct and indirect relationships among variables. The results show that FDI, labor force participation, and trade openness have a significant positive effect on exports, while exchange rates show a negative relationship. Furthermore, exports play a significant mediating role in transmitting the effects of FDI and trade openness on economic growth. These findings highlight the importance of strengthening export performance through supportive investment policies, stable exchange rates, and increased labor productivity to achieve sustainable economic growth in Indonesia.